Academic Standards and Cultural Reproduction in Accounting Education - Nelwan, Melinda Lydia (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
The purpose of this research paper is to explore the association between academic standards and cultural background.  Particularly, it is to answer the question of whether the Australian educational culture is being reproduced in the accounting education in Australia.  The research method for this study is focus groups of domestic and international undergraduate Accounting students of the Australian National University.  The results show that in certain aspects the academic standards are biased towards domestic students.  There is evidence that the Australian educational culture has been reproduced in the accounting education through the imposition of academic standards.  Several studies have been conducted to examine the impact of academic standards in accounting education, but little attention has been paid regarding cultural reproduction in the Australian education system, particularly within the scope of accounting education.  This study contributes to provide better understanding concerning this topic and the findings give input to the standard setters to develop academic standards which facilitate participation of more diverse culture.